Gestão dos dispositivos de comunicação da web social: potencializando as atividades de mediação da informação e do conhecimento em bibliotecas universitárias brasileiras - Santos, Raquel do Rosário (2016)
Communication devices are the social web 'actions in the library, making them closer to the users, to improve the interaction between them beyond physical environment of the library. Communication devices, as provided by libraries, can give greater visibility to the activities of the library, expanding the possibilities for dissemination and access to information. In this study a model for managing communication devices provided in the social web by university libraries based on information and knowledge management developed. He offered theoretical and methodological support to promote the effectiveness of mediation business information. It is characterized as a theoretical and empirical research, because, at first was supported in the literature to achieve the objective referred to the construction of indicators that support the proposal of a model for the management of communication devices social web provided by university libraries. Subsequently, the necessity of a rapprochement with the object of research and investigation can characterize it as an empirical reality. Both empirical and theoretical foundation will support research on how the management of information and knowledge can contribute to improving mediation business information communication devices of social web provided by university libraries. The model consists of six (6) central themes: strategic planning, organizational culture and information, infrastructure, information literacy, knowledge of the organization and evaluation. Since these issues was also possible to identify the components that integrate and their basis: management policy communication devices of the social web, participation, sharing, people, technology infrastructure, content, learning, needs and expectations of users and partners. It is considered that the mediation efforts of information and knowledge in the hands made by librarians in communication devices in the social web should be planned and the procedures for its implementation must be registered with the management policy, so level national in this process so as to realize standard in university libraries. The results show that university libraries to worship the manner of communication devices are contributing to improving mediation efforts of information and knowledge.